Theories of personality as a methodological basis for organizing nonformal education in the social sphere - Nadiya Pavlik (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The results of analysis of psychological and sociological theories of personality are presented in this article. Analysis is done under the scheme: the main idea of the theory, the structure of personality concept, principles of motivation of the individual's activity through the prism of their usage for organizing nonformal education of students. Contradiction between individual and social motives is highlighted; personality in the system of social institutions is characterized. Resources and potentiality of nonformal forms of educational activities for meeting the needs, interests and goals in the educational environment are designed. Сonclusion on the need of introduction in the process of professional training the nonformal education for consideration of motivation of the individual is done.
Keywords: personality; theory of personality; nonformal education; formal education